Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the derivative of $3sin^2(6x)$. I know I solve this by using chain rule, my question is how come product rule is not used instead on $3$ and $sin^2(6x)$? According to wolfram alpha, the constant is factored out at the beginning of the problem, if that is the case: how come you just wouldn't factor the constant out of all derivative questions?

share|cite|improve this question
because the derivative of a constant is 0, and thus that term cancels? – Roger Apr 4 '14 at 20:36
You can use the product rule if you look at the $3$ as the function $x\mapsto 3$. It is also legal to factor it out. – Git Gud Apr 4 '14 at 20:36
how come you just wouldn't factor the constant out of all derivative questions?: you seem to be mistaken. We most definitely can. Could you show an example where you think we cannot?(not rhetoric, we need to see your doubt to clear it) – Sabyasachi Apr 4 '14 at 20:42
$$\frac{d}{dx}(3 f(x)) = 3 \frac{d}{dx} (f(x)) + f(x) \frac{d}{dx}(3) = 3 f'(x)+0 = 3 f'(x)$$ – Henry Apr 4 '14 at 20:47
@Henry Wow, this stuff is like magic! – chopper draw lion4 Apr 4 '14 at 20:54
up vote 6 down vote accepted

If you'd like to use the product rule, then use the product rule. Let's do it now.

The $(fg)' = f'g + fg'$, so $$\frac{d}{dx} 3\sin^2(6x) = \left(\frac{d}{dx} 3\right) \sin^2(6x) + 3\left(2\sin(6x)\cos(6x)6\right) = 0 + 3\left(12\sin(6x)\cos(6x)\right).$$

You'll notice that it's just as if the $3$ factored out. While I'd recommend recognizing that you can pull constants out, it is entirely possible to use the product rule every time.

You also ask: How come you wouldn't always pull the constant out? My answer - I always would pull the constant out. Let's even prove that this happens:

A derivative of a function $f$ is

$$\lim_{h \to 0} \frac{f(x+h) - f(x)}{h},$$

so that

$$ \frac{d}{dx} cf(x) = \lim_{h \to 0} \frac{cf(x+h) - cf(x)}{h} = c\lim_{h \to 0} \frac{f(x+h) - f(x)}{h} = cf'(x).$$

More generally, differentiation is a linear operator, meaning that $(af(x) + bg(x))' = af'(x) + bg'(x)$ for any functions $f,g$ and constants $a,b$.

share|cite|improve this answer
Eureka! I have asked many professors at my University this question and all of them gave conflicting answers. This is the best one I have heard. Everything makes sense now and I can rest peacefully. Thank you @mixedmath – chopper draw lion4 Apr 4 '14 at 21:14

As @GitGud points out, you can use the product rule. But the result is the same every time. If $c$ is a constant and $f$ is a function, then you always find that, using the product rule (and the fact that $c$ has a derivative of $0$)

$$\boxed{(c\cdot f(x))'} = c'\cdot f(x) + c\cdot f'(x) = 0\cdot f(x) + c\cdot f'(x)=\boxed{c\cdot f'(x)}$$

In other words, as you also asked, you can indeed pull any constant factor out front and take the derivative of what remains.


$$(7x^2)'=7(x^2)' = 7(2x)=14x$$

$$\left(\frac23\sin5x\right)'=\frac23(\sin5x)' = \frac23(\cos 5x\cdot 5)=\frac{10}{3}\cos5x$$

$$(3\sin^2 6x)'= 3(\sin^2 6x)' = 3(2\sin 6x\cdot\cos6x\cdot6)=36\sin 6x\cos6x $$

It is even more generally true that differentiation is a linear operator, in the sense that for constants $a$ and $b$ it is true that

$$(a\cdot f(x)+b\cdot g(x))' = a\cdot f'(x) + b\cdot g'(x)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.